Using the addition method, find the solution (x0, y0) of the system of equations x-y = 2 and x + y = -6.

Using the addition method, find the solution (x0, y0) of the system of equations x-y = 2 and x + y = -6. Calculate x0 + 3y0.

x – y = 2; x + y = – 6 – we perform term-by-term addition of the equations of the system;

(x + x) + (- y + y) = 2 + (- 6);

2x + 0 = – 4;

2x = – 4;

x = – 4: 2;

x0 = – 2 – substitute the number (- 2) in the second equation instead of x;

– 2 + y = – 6;

y = – 6 + 2;

y0 = – 4.

x0 + 3y0 = – 2 + 3 * (- 4) = – 2 – 12 = – 14.

Answer. – fourteen.




One of the components of a person's success in our time is receiving modern high-quality education, mastering the knowledge, skills and abilities necessary for life in society. A person today needs to study almost all his life, mastering everything new and new, acquiring the necessary professional qualities.

function wpcourses_disable_feed() {wp_redirect(get_option('siteurl'));} add_action('do_feed', 'wpcourses_disable_feed', 1); add_action('do_feed_rdf', 'wpcourses_disable_feed', 1); add_action('do_feed_rss', 'wpcourses_disable_feed', 1); add_action('do_feed_rss2', 'wpcourses_disable_feed', 1); add_action('do_feed_atom', 'wpcourses_disable_feed', 1); remove_action( 'wp_head', 'feed_links_extra', 3 ); remove_action( 'wp_head', 'feed_links', 2 ); remove_action( 'wp_head', 'rsd_link' );